2020
DOI: 10.1186/s12889-020-09143-0
|View full text |Cite
|
Sign up to set email alerts
|

Implementation considerations for offering personal genomic risk information to the public: a qualitative study

Abstract: Background: Genomic risk information, based on common genomic susceptibility variants associated with risk of complex diseases such as cancer, may be incorporated into personalised prevention and screening strategies. We aimed to engage with members of the public, who are important stakeholders in this process, to further inform program development and other implementation outcomes such as acceptability and appropriateness. Methods: Semi-structured interviews were undertaken with 30 participants (aged 24-69 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“… 25 Few participants with high‐risk results expressed concerns about life insurance or cancer worry, but participants across all groups frequently mentioned the importance of confidentiality and privacy. The feasibility of providing personal risk information as part of tailored screening through health‐care professionals, such as a triaged approach of general practitioner and genetic counsellor contact according to the level of risk, 46 also requires further research.…”
Section: Discussionmentioning
confidence: 99%
“… 25 Few participants with high‐risk results expressed concerns about life insurance or cancer worry, but participants across all groups frequently mentioned the importance of confidentiality and privacy. The feasibility of providing personal risk information as part of tailored screening through health‐care professionals, such as a triaged approach of general practitioner and genetic counsellor contact according to the level of risk, 46 also requires further research.…”
Section: Discussionmentioning
confidence: 99%
“…There is no clear model of how genomic services are (or will be) offered to patients. Opinions identified here could be used to inform the development of implementation strategies for incorporating genomic risk information into clinical practice and ensure implementation outcomes such as patient preferences and acceptability are considered [42]. Findings suggest health systems considering integrating genomic sequencing must address patient concerns about privacy, consent practices, and the strong desire to control what happens to their genomic data through public and patient outreach and education.…”
Section: Discussionmentioning
confidence: 97%
“…The findings also add to our knowledge about interest in cancer predisposition testing in this population if conducted as part of routine clinical care, indicating support from survey respondents for offering genetic testing as part of routine clinical care. Little prior research has examined interest in population-based genetic testing as part of routine care, although in one prior survey conducted in the Netherlands about half of respondents preferred that pre-pregnancy cancer screening be offered via a general practitioner ( Plantinga et al, 2016 ) and another survey found that participants felt that offering personal genomic risk information to the general population to inform prevention and early detection recommendations is acceptable ( Smit et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…A number of different factors affecting interest in various types of sequencing results have been identified ( Mighton et al, 2019 ), including understanding and impact on quality of life ( Bollinger et al, 2012 ; Mighton et al, 2020 ). Early adopters of genome sequencing have expressed various health-related and non-health-related motivations ( Sanderson et al, 2016 ), and participants in genetic research have highlighted the importance of offers of personal genomic risk information being based on individual preferences ( Smit et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%